KETERKAITAN DINAMIS FAKTOR FUNDAMENTAL MAKROEKONOMI DAN IMBAL HASIL SAHAM - ENDRI ENDRI (Jurnal Bisnis dan Akuntansi, 2009)
This paper investigation empirically the dynamic inter-dependence of the maroeconomy variables and stock returns with data the during period 2003 until 2008. Empirical investigation is conducted by the cointegration Engle-Granger method, error correction mechanism, and regression analysis. Result show significant long-run and short-run relationship between macroeconomic variable and stock returns.